Sensitivity Analysis of Transonic Flow over J-78 Wings - Alexander Kuzmin (International Journal of Aerospace Engineering)
3D transonic flow over swept and unswept wings with an J-78 airfoil at spanwise sections is studied numerically at negative and vanishing angles of attack. Solutions of the unsteady Reynolds-averaged Navier-Stokes equations are obtained with a finite-volume solver on unstructured meshes. The numerical simulation shows that adverse Mach numbers, at which the lift coefficient is highly sensitive to small perturbations, are larger than those obtained earlier for 2D flow. Due to the larger Mach numbers, there is an onset of self-exciting oscillations of shock waves on the wings. The swept wing exhibits a higher sensitivity to variations of the Mach number than the unswept one.